(untitled) (Physical Education, Health and Social Sciences, 2025)
This research paper investigates a historical appraisal of Sufi legacy of Hazrat Nizamuddin Auliya (1238–1325), as a leading Sufi saint of the Indian subcontinent, focusing on his life, spiritual practices, discipleship, poetry, and socio-cultural impact. Through qualitative analytical approach of research, the study traces his early life in Badayun, formative education under distinguished scholars, and migration to Delhi for higher learning, highlighting the influence of his mother, Bibi Zulaikha, and early teachers in shaping his moral and intellectual development and further examines his interactions with Delhi Sultanate rulers, including Alauddin Khalji, Ghiyath-ud-Din Tughlaq, and Khusro Khan, demonstrating how he maintained spiritual independence while ethically guiding political and social affairs. The paper explores his rigorous spiritual disciplines, asceticism, devotional routines, and charitable activities, showing how his khanqah became a center of worship, learning, and social reform. Anecdotes from disciples illustrate his pedagogical methods, personal virtues, and exemplary behavior, while thematic analysis of his poetry emphasizes motifs of divine love, ethical conduct, mortality, and mystical experience. The study concludes that Hazrat Nizamuddin Auliya embodied a holistic Sufi model, integrating devotion, scholarship, ethical guidance, social service, and cultural contribution. The question that has been addressed in the paper is that how the teachings of this saint profoundly shaped medieval India’s spiritual, social, and literary landscapes, leaving a lasting legacy of devotion, morality, and cultural expression?